Psychometric properties of the Propensity to Morally Disengage Scale in Peruvian university students: internal structure and association with the dark triad - Lingán-Huamán, Susana K.; Dominguez-Lara, Sergio; Serpa-Barrientos, Antonio (Frontiers in Education, 2023)
This study aimed to analyze the psychometric properties of the Propensity to Morally Disengage Scale in Peruvian university students. The number of university students who participated in the study was 591 (women = 71.7%; Mage = 21.5; SDage = 3.60). The results showed a unidimensional structure in both men and women. As for the invariance results according to sex, there is a favorable evidence of configural and weak invariance; however, there is no evidence of strong invariance. Furthermore, the reliability of the construct (coefficient ω) and its scores (coefficient α) reached acceptable dimensions in each group and positive associations with the dark triad (Machiavellianism, psychopathy, and narcissism). The theoretical and practical implications are discussed.